2018
DOI: 10.1590/1678-457x.14417
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multimode ultrasound assisted extraction on the yield of crude polysaccharides from Lycium Barbarum (Goji)

Abstract: The goals of this exploration were to find out the optimum conditions of ultrasound assisted extraction (UAE) of L. Barbarum crude polysaccharides. Furthermore, to research the impacts of three multi-frequency ultrasound assisted extraction modes on the yield of L. Barbarum crude polysaccharides. The results showed that by applying the traditional single-frequency UAE mode, the optimum extraction time was 30 min, extraction temperature of 60 °C, and solid/liquid ratio of 20 g/600 mL, at a power density of 300 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…The aforementioned could explain the reason for the high yield at a dual‐frequency of 20–40 kHz. The result is supported by that of Muatasim et al (), who reported that enhanced cavitation efficiencies in dual‐frequency (20–40 kHz) resulted in a significant yield of 38.93% crude polysaccharides from Lycium barbarum .…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The aforementioned could explain the reason for the high yield at a dual‐frequency of 20–40 kHz. The result is supported by that of Muatasim et al (), who reported that enhanced cavitation efficiencies in dual‐frequency (20–40 kHz) resulted in a significant yield of 38.93% crude polysaccharides from Lycium barbarum .…”
Section: Resultssupporting
confidence: 76%
“…However, this technique has been associated with initiating the degradation of polysaccharides due to prolonged ultrasonic treatment (Dong et al, ). In recent times, alternative modes to mono frequency irradiation such as dual‐frequency (DFu) have emerged and reported to have a better cavitation and product yield through a simultaneous effect of low and high frequencies (Muatasim, Ma, & Yang, ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have recently shown that a multi‐frequency US method had better treatment efficiency than single‐frequency US method, such as in the degree of hydrolysis of casein, the extraction of biomacromolecules, and the structure modification of gluten protein (Muatasim et al., 2018; B. Xu et al., 2020; H. Zhang, Chen, et al., 2020). Phyllis Naa Yarley et al.…”
Section: Ultrasoundmentioning
confidence: 99%
“…The authors demonstrated that ultrasonic-treated CPs exhibited better emulsifying properties in an oil-in-water emulsion system but weaker rheological and gelling properties than the original CPs, mainly due to their molecular weight and chain conformations than the others (e.g., galacturonic acid content, DM, and amount of neutral sugar side chains). Some studies have recently shown that a multifrequency US method had better treatment efficiency than single-frequency US method, such as in the degree of hydrolysis of casein, the extraction of biomacromolecules, and the structure modification of gluten protein (Muatasim et al, 2018;B. Xu et al, 2020;…”
Section: Us Modification Of Polysaccharidesmentioning
confidence: 99%
“…LBP can promote the immune function of T, B, CTL, NK and macrophages, promote the production of cytokines such as IL-2, IL-3 and TNFβ, enhance the immune function of tumor-bearing, chemotherapy and radiation-damaged mice, and regulate neuroendocrine immune regulatory network (Muatasim et al, 2018). However, whether LBP has a protective effect in T2D-induced neuronal axonal transport disorder, or whether it can improve the impaired axonal transport, has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%